Rheological redistribution of stresses in multi-layered beams = Reologiczna redystrybucja naprężeń w belkach wielowarstwowych - Socha, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper concerns problems of rheology in wooden structures reinforced with polyester-glass composite bars glued to them by means of epoxy resin. A theoretical model of the behaviour of a multi-layered beam is presented. The component materials of this beam are described with equations for linear viscoelastic media (five- and sixparameter rheological models).
Keywords: belki wielowarstwowe; reologia; redystrybucja naprężeń; pręty kompozytowe; multi-layered structures; redistribution of stresses; rheology; viscoelasticity